Information System-Based Principal Management in Managing Education - Hasanah, Ummi Uswatun; Swandari, Tatik (Universitas KH. Abdul Chalim Pacet Mojokerto, 2023)
This article aims to describe and analyze the principal's management information system in education management at SMP Islahiyah Klenang Kidul Banyuanyar Probolinggo. The method used is qualitative with a case study approach. Interviews were conducted with informants, namely the principal, information management staff, administration, and several teachers. The results of this article are as follows: The role of SIMPs in the field of curriculum shows that 73% of SIMPs play a role while 27% do not. The role of SIMP in the field of educators and education plays a 100% role. 3) The role of SIMP in the field of students shows that 93% have a role and 7% do not.